GE_GERICHTE P/9878/2004 vom 3. April 2008 - GE Cour de justice (2008)
; SÉQUESTRE(MESURE PROVISIONNELLE) ; CRÉANCE ; COMPÉTENCE RATIONE MATERIAE ; PERSONNE CONCERNÉE ; SUBSIDIARITÉ | CPP.115A.1; CP.70; CP.71